Evaluation of Quality of Primary Health Care Services at Primary Health Care Centers in Baghdad City: A Comparative Study - jassim, basima; Khalifa, mohammed (Iraqi National Journal of Nursing Specialties, 2018)
Objective(s): To evaluate primary health care services at primary health care centers in Baghdad City and to compare between these primary health care centers relative to such quality. Methodology: A descriptive design, using the evaluation approach, is study to Evaluation of quality of primary care services at primary health care centers in Baghdad City. A multistage probability sample of (36) health care centers was selected. The sample consists of (12) model centers, (12) urban centers, and (12) rural centers.A constructedquestionnaire is composed of (23) items. It consisted of (5) parts that include intangible (5) items, reliability (5) items, response (4) items, emphasis and confidence (4) items and sympathy (5) items. Validity and reliability of the questionnaire are determined through pilot study. Data are collected through the use of the questionnaire and the interview technique as a means of data collection. Data are analyzed through the application of descriptive statistical data analysis approach of frequency, percentage, mean, range and total scores and inferential statistical data analysis approach of analysis of variance (ANOVA). Results: Findings of the study indicate that the primary health care services at most of the primary health care centers have high quality and there is no difference between the primary health care centers based on such quality. Recommendations: Managers of primary health care centers can be specialized with high degrees for better quality of primary health care services. Females can be presented with more opportunities to be managers. Periodic evaluation of primary health care services can be employed. Further and nation-wide research studies can be conducted for the determination of the quality of primary health care services.